Influence of external field and consequent impurity breathing on excitation profile of doped quantum dots - Pal, Suvajit; Ghosh, Manas (Journal of luminescence, 2013)
Excitation in quantum dots is an important phenomenon. Realizing the importance we investigate the excitation behavior of a repulsive impurity doped quantum dot induced by an external oscillatory field. As an obvious consequence the simultaneous oscillation of spatial stretch of impurity domain has also been taken into account. The impurity potential has been assumed to have a Gaussian nature. The ratio of two oscillations (η) has been exploited to understand the nature of excitation. Indeed it has been found that the said ratio could orchestrate the excitation in a truly elegant way. Apart from the ratio, the dopant location also plays some meaningful role towards modulating the excitation rate. The present study also indicates the attainment of stabilization in the excitation rate as soon as η surpasses a threshold value irrespective of the dopant location. Moreover, prior to the onset of stabilization we also envisage minimization in the excitation rate at some typical η values depending on the dopant location. The critical analysis of pertinent impurity parameters provides important perception about the physics behind the excitation process. ► The excitation profile of impurity doped quantum dot has been investigated. ► The dot is subject to external oscillatory field. ► Concomitant time-dependence in spatial stretch of impurity has been introduced. ► Minimization in excitation rate is observed as a function of two oscillation ratios. ► Role of dopant location has also been analyzed.